Pengujian Beban Kerja Sebagai Variabel Intervening dalam Hubungan Ambiguitas Peran dan Budaya Organisasi Terhadap Stres Kerja pada Tenaga Kesehatan Di Rumah Sakit Angkatan Darat X - Clarisa Clarisa; Nofierni Nofierni; Sandra Dewi (Jurnal Health Sains, 2022)
Human resources are the most important asset in the organization because of the role of employees in maintaining and improving performance. Job stress is a situation related to work factors that can cause changes to a person's psychological or physiological condition. The purpose of this study was to analyze the effect of role ambiguity and organizational culture on work stress with workload as an intervening variable on health workers at Army Hospital X. The method in this study was quantitative associative using a questionnaire given to health workers at Army Hospital X. Statistical analysis using Pearson correlation test followed by multiple linear regression test with and without workload variables. Pearson correlation test analysis shows the correlation coefficient between variables is greater than 0.60 (significance level <0.001) so that there is a relationship between the variables tested. The results of multiple linear regression test with a workload variable determination coefficient of 0.611, while without a workload variable of 0.603. There is a significant influence between variables in this study. Role ambiguity, workload, and organizational culture have an effect on work stress together. However, the role of the workload variable becomes small or even disappears because the influence of the role ambiguity variable and organizational culture on work stress is very large. The beta coefficient of organizational culture is the largest (0.311) among the other two variables so that organizational culture is the variable that has the most influence on the emergence of work stress. Role ambiguity and organizational culture have a significant effect on work stress, while workload is not an intervening variable for health workers at Army Hospital X